Family-supportive supervisor behaviors and career sustainability of e-commerce female workers: A mixed-method approach - Luo, Huan; Li, Fa; Agbanyo, George Kwame; Tachega, Mark Awe; Chin, Tachia (Frontiers in Psychology, 2022)
Females play an essential role in promoting societal and economic harmony development. However, compared with males, female employees usually have to take more family responsibilities while they endeavor to perform well at work. It is inevitable for them to face work-family conflicts, therefore how to make female employee career more sustainable is a critical concern. Even though female career sustainability is well explored in literature, the combined effect of worker self-efficacy and family-supportive supervisor behaviors (FSSB) on female career sustainability remains unexplored. To fill this gap, this study examines the influence of FSSB on female employee career sustainability, as well as the mediating role of self-efficacy. Moreover, a mixed-method approach was used to test the proposed relationships. The results indicate that FSSB has a positive impact on female career sustainability. Furthermore, the findings revealed that FSSB promotes female career sustainability through self-efficacy. This study establishes a theoretical framework for further research on the relationships between leader behavior and employee career sustainability. At the same time, it offers practical implications for supervisors in management of subordinate career sustainability.